SILKWORM REARING PRACTICES IN RURAL PAKISTAN - Faiz Ur RAHIM; Muhammad Farooq HYDER; Madiha ASMA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Silkworm rearing practices can play an important role in the well-being of deprived rural populations and boost the growth of economy. It is a simple and short tenure process and contains a sensitive series of activities. Silkworm rearing practices made marvellous progress in early eras of liberation. Currently, however, this industry is almost obsolete. The present study explores the silkworm rearing process, practiced by Pakistani farmers. This study is purely based on primary data and was also supported by secondary data from literature. Results of the study indicate that although Pakistani silk farmers have sufficient knowledge and experience but they need a proper support and assistance from state department to convert the sericulture industry into a profitable industry.